Evaluation of arbuscular mycorrhiza with symbiotic and nonsymbiotic pea isolines at three sites in the Alentejo, Portugal - Kleikamp, Bernd; Joergensen, Rainer Georg (Journal of Plant Nutrition and Soil Science, 2006)
Providing an appropriate negative control for the experimental factor arbuscular mycorrhiza (AM) is a fundamental methodological problem. Therefore, the nonmycorrhizal (myc – ) and nonnodulating (nod – ) pea (Pisum sativum L.) mutant P2 was studied together with the parental symbiotic isogenetic variety FRISSON in three experiments: (1) growth response to water supply in a climate chamber under nonsymbiotic growth conditions, (2) field evaluation at three sites in the Alentejo, South Portugal, and (3) growth response to P supply in a soil low in available P in a greenhouse-chamber experiment. In the climate chamber at high NPK levels, mutant P2 achieved the same biomass as FRISSON at 80% and 40% water-holding capacity, respectively. For the field evaluation, three sites were chosen with normal arable use (Évora), extensive use as Montado (Portel), and intensive horticultural use (Mitra). The colonization of pea roots with AM fungi ranged from 4% (Mitra) to more than 90% (Portel), probably caused by differences in P availability. The plant density of mutant P2 was generally 25% lower than that of FRISSON. Yield indices were all lowest at Portel, despite the same NPK fertilization. Grain and shoot yield of mutant P2 did not reach the level of FRISSON at any site. Differences in N and P concentrations between the two isolines were insignificant in most cases. Differences in the amount of shoot P per plant consistently mirrored the mycorrhizal status of the three sites. Roughly 50% of the yield depression per m2 could be attributed to the lower plant density of mutant P2, the remaining 50% must be caused by AM-fungal colonization or other factors. In the final pot experiment using the soil with low P availability from Portel, the main benefit of AM for peas was enhanced P uptake. Central questions could not be answered using a nonmycorrhizal control. However, mutants remain one interesting tool, best be used in combination with other approaches to estimate the effects of mycorrhization.
Keywords: amf; arbuscular mycorrhiza; growth response; mediterranean dryland farming; myc-mutant; p and n nutrition; pea